Pressing the police and policing the press: the history and law of the U.S. press-police relationship - Memmel, Scott (Journalism in perspective: continuities and disruptions, 2024)
"This book provides an in-depth examination of the centuries-long relationship between the press and the police in the United States and its contemporary legal landscape, revealing significant implications in the present and future for these fundamental institutions, their relationship, and the public"--